2018
DOI: 10.1371/journal.pone.0195295
|View full text |Cite
|
Sign up to set email alerts
|

Evicted children and subsequent placement in out-of-home care: A cohort study

Abstract: BackgroundEvictions may have serious consequences for individuals’ health and wellbeing. Even though an eviction may be experienced as a significant crisis for the family, there is little previous knowledge on consequences for evicted children. This study represents the first attempt to examine to what extent children from evicted households were separated from their parents and placed in out-of-home care (foster family or residential care) using population-based data, net of observed confounding factors relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…One relatively small study in Michigan during the 2008 recession found that eviction was associated with anxiety attacks; however, health effects were generally not found when controlled for income and prior health (Burgard et al, 2012). Children of evicted families are substantially more likely to be taken into care or removed from their parents (Berg & Brannstrom, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One relatively small study in Michigan during the 2008 recession found that eviction was associated with anxiety attacks; however, health effects were generally not found when controlled for income and prior health (Burgard et al, 2012). Children of evicted families are substantially more likely to be taken into care or removed from their parents (Berg & Brannstrom, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…According to a systematic review of 47 studies, individuals affected by foreclosure reported a higher frequency of depression, anxiety, psychological distress, and suicide compared with the general population or people who did not have these experiences. Foreclosure has an impact on the health and well-being of all members of the family, particularly children [38]. Examining possible pathways between home foreclosure and mental health, Vasquez-Vera [22] proposed that housing insecurity acts as a stressor that increases the incidence of major depression and generalized anxiety disorder, as demonstrated in the United States [39].…”
Section: Discussionmentioning
confidence: 99%
“…This vein of research is lacking in unity and clarity regarding which terms to use to describe similar concepts. For example, RCCs were termed 'institutional care' (Baptista et al, 2019), 'residential care' (Lukšík, 2018), 'orphanage' (Adejuwon & Oki, 2011), 'out-of-home care' (Berg & Brännström, 2018) and 'children's home' (Abd Rahman et al, 2013). Some individuals may consider these terms to indicate the same care setting, while others may consider them distinct.…”
Section: Terminology and Methodologymentioning
confidence: 99%